Tactile "capture" of audition. - Caclin, A; Soto-Faraco, S; Kingstone, A; Spence, C (2002)
Previous research has demonstrated that the localization of auditory or tactile stimuli can be biased by the simultaneous presentation of a visual stimulus from a different spatial position. We investigated whether auditory localization judgments could also be affected by the presentation of spatially displaced tactile stimuli, using a procedure designed to reveal perceptual interactions across modalities. Participants made left-right discrimination responses regarding the perceived location of sounds, which were presented either in isolation or together with tactile stimulation to the fingertips. The results demonstrate that the apparent location of a sound can be biased toward tactile stimulation when it is synchronous, but not when it is asynchronous, with the auditory event. Directing attention to the tactile modality did not increase the bias of sound localization toward synchronous tactile stimulation. These results provide the first demonstration of the tactile capture of audition.